2015
DOI: 10.1001/jamapediatrics.2014.3736
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Community Therapists’ Use of Therapy Techniques in a Large Public Mental Health System

Abstract: Importance Few studies have examined the effects of both clinician and organizational characteristics on the use of evidence-based practices in mental healthcare. Improved understanding of these factors could guide future implementation efforts to ensure effective adoption, implementation, and sustainment of evidence-based practices. Objective To estimate the relative contribution of clinician and organizational factors on clinician self-reported use of cognitive-behavioral, family, and psychodynamic techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 36 publications
13
149
1
Order By: Relevance
“…However, a few clinicians used PE much more widely, treating 8-20 patients at a time. Other studies have also found that even if clinicians' attitudes and intentions are highly positive, organizational and contextual factors may limit how much they can use a new treatment (Aarons et al 2011;Beidas et al 2015;McHugh and Barlow 2010). Consistent with other research on clinician behavior (Couineau and Forbes 2011;Godin et al 2008), we found that intent to use and actual use of PE were partially determined by clinicians' outcome expectancies, self-efficacy, and control beliefs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, a few clinicians used PE much more widely, treating 8-20 patients at a time. Other studies have also found that even if clinicians' attitudes and intentions are highly positive, organizational and contextual factors may limit how much they can use a new treatment (Aarons et al 2011;Beidas et al 2015;McHugh and Barlow 2010). Consistent with other research on clinician behavior (Couineau and Forbes 2011;Godin et al 2008), we found that intent to use and actual use of PE were partially determined by clinicians' outcome expectancies, self-efficacy, and control beliefs.…”
Section: Discussionsupporting
confidence: 88%
“…This evaluation largely limited its focus to clinician factors. We did not assess patient receptivity to PE (Kehle-Forbes et al 2014;Mott et al 2014;Watts et al 2015), nor did we assess contextual factors such as leadership support, team environment, staffing levels, or local clinic infrastructure (Aarons et al 2011;Beidas et al 2015;Cook et al 2015). Such factors are beyond the scope of this evaluation, but may be important to broader VHA efforts to expand veteran access to effective PTSD treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confidence with TF-CBT components, attitudes toward EBTs, and problematic productivity requirements were not predictive of these outcomes. Finally, our predictors were not significant for our third outcome, the use Beidas et al's (2015) finding that MHPs' greater openness to trying EBPs was predictive of CBT technique use.…”
Section: Full Sample Findingsmentioning
confidence: 57%
“…Potential explanatory variables not assessed in this study include factors such as agency support for TF-CBT and/or EBTs in general, therapist prior experience with EBTs, and therapist training in trauma-related interventions. In particular, more extensive examination of agency factors might have yielded stronger predictive ability, as indicated by Beidas et al's (2015) finding that organizational factors were more strongly predictive of EBP use than individual factors.…”
Section: Unexplained Variancementioning
confidence: 99%